Kontribusi Pemikiran Ibnu Rusyd terhadap Paradigma Pendidikan Islam Berbasis Intelektual dan Rasional - Annisa Maryam Nurrohmah; Masnu’atul Khoiriyah; Hasnun Umar; Emilia Nurwati; Febry Suprapto (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to analyze the biography, intellectual thought, and Islamic educational paradigm of Ibn Rushd (Averroes) and to examine its relevance to contemporary Islamic education, which continues to struggle with normative-dogmatic tendencies and the limited development of critical rationality. This research employed a qualitative approach with a case study design. Data were collected through content analysis of Ibn Rushd’s major works, including Tahāfut al-Tahāfut and Faṣl al-Maqāl, supported by secondary sources such as academic books and peer-reviewed journal articles, as well as interviews with Islamic education scholars and practitioners. The data were analyzed using interpretative and discourse analysis techniques, complemented by source triangulation to ensure validity. The findings reveal that Ibn Rushd positioned reason and revelation as complementary epistemological foundations in Islamic education. Intellectuality, in his perspective, encompasses rational, moral, and spiritual dimensions, aiming at the perfection of the human soul. Furthermore, Ibn Rushd’s educational paradigm emphasizes critical thinking, dialogical learning, and the integration of religious and empirical sciences, while rejecting rigid dogmatism. This study concludes that Ibn Rushd’s rational-integrative framework remains relevant as an alternative conceptual foundation for reforming contemporary Islamic education toward a balanced integration of faith, knowledge, and rationality.